Collaborative Efforts of Counseling Teachers in Enhancing Self-Happiness Among Qur'an- Memorizing Students: A Case Study - Beni Azwar (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the collaboration between Counseling Guidance (CG) teachers and tahfidz teachers in enhancing the self-happiness of students memorizing the Qur'an at SDIT Robby Radiyah. Self-happiness is crucial for effective Qur'anic memorization, given the demanding nature of the task, which requires focus, concentration, and emotional well-being. A descriptive qualitative approach was employed. Data were collected through interviews, observations, and document analysis, using purposive sampling that included the principal, two CG teachers, five tahfidz teachers, and students. Source triangulation involving the foundation and parents was utilized to ensure validity, and findings were presented descriptively. The study found that CG teachers, through counseling services, addressed students' boredom, stress, and emotional challenges. Concurrently, tahfidz teachers implemented a fun yet disciplined approach to guide memorization. This collaborative effort, reinforced by parenting, social support, and diverse activities, created a supportive environment that fostered happiness, motivation, and emotional well-being in students. The synergy between CG and tahfidz teachers, combined with external support systems, plays a pivotal role in promoting students' self-happiness, thereby enhancing their ability to memorize the Qur'an effectively. Collaboration between CG and tahfidz teachers, supported by parenting and social factors, significantly contributes to the self-happiness and motivation of students memorizing the Qur'an, highlighting the importance of an integrated approach to holistic educational success.